Revitalization Of Socio-Cultural Values In Pesantren - Nenden Munawaroh; Ijudin Ijudin; Hilda Ainissyifa; Nurul Fatonah (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This article aims to explain the importance of returning socio-cultural values of Islamic education in the learning process in pesantren, as a model of Islamic education that is humanist and inclusive, and upholds socio-cultural values. The method used in this article is to use a qualitative-analytical approach with a descriptive method. The results of the discussion show: (1) That the socio-cultural values of Islamic education in pesantren are very vital and their presence is needed to produce humanist and inclusive students, (2) Integration of socio-cultural values of Islamic education in the learning process in pesantren, by integrating religious values, culture, and diversity, (3) The integration gives birth to socio-cultural values, such as respecting differences in schools of thought in worship practices, assimilation between cultures and regional languages, tolerance and human rights, and social coherence between students